2017
DOI: 10.18410/jebmh/2017/314
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Diastolic Dysfunction in Patients of Type-2 Diabetes Mellitus in Rural Population of Western Uttar Pradesh

Abstract: BACKGROUND Diabetes mellitus is a disease with multisystem involvement. Most common cardiovascular complications of diabetes mellitus is the presence of diabetic cardiomyopathy. Diastolic left ventricular dysfunction may be early sign of diabetic cardiomyopathy, which is easily accessed by echocardiography. The aim of the study is to study the prevalence of left ventricular diastolic dysfunction (LVDD) in asymptomatic, nonhypertensive patients of diabetes mellitus. MATERIALS AND METHODS A study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[7] Also, the prevalence of hospitalizations due to HFpEF comparative to heart failure with reduced ejection fraction (HFrEF) is increasing at a rate of 1% per year. [5]…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Also, the prevalence of hospitalizations due to HFpEF comparative to heart failure with reduced ejection fraction (HFrEF) is increasing at a rate of 1% per year. [5]…”
Section: Epidemiologymentioning
confidence: 99%
“…[4] It is known that approximately, 50% cases of DM suffer from heart failure with preserved ejection fraction (HFpEF). [5] Therefore, DM has been perceived as a responsible factor for HF.…”
Section: Introductionmentioning
confidence: 99%
“…The Framingham study showed that the development of HF is two times more likely in men with diabetes and five times more likely in women with diabetes after adjustment for other risk factors, including age, coronary heart disease, and hypertension [2]. It is also known that approximately 50% of cases of diabetes mellitus (DM) suffer from HF with preserved ejection fraction (HFpEF) [3]. Therefore, DM has been perceived as a factor responsible for HF.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Hyperglycemia is an independent risk factor for ischemic heart disease (IHD) as several mechanisms lead to vascular damage due to long-term hyperglycemia. 8,9 To clarify the mechanisms responsible for decreased myocardial contractility in the diabetic population, several explanations have been proposed. 10,11 In patients with diabetes, altered metabolism has been associated with increased myocardial oxygen consumption and increased serum free fatty acid (FFA) concentrations.…”
Section: Introductionmentioning
confidence: 99%